Hexacyanoferrate‐adapted biofilm enables the development of a microbial fuel cell biosensor to detect trace levels of assimilable organic carbon (AOC) in oxygenated seawater. Issue 12 (5th August 2014) - Cheng, Liang; Quek, Soon Bee; Cord‐Ruwisch, Ralf
ABSTRACT A marine microbial fuel cell (MFC) type biosensor was developed for the detection of assimilable organic carbon (AOC) in ocean water for the purpose of online water quality monitoring for seawater desalination plants prone to biofouling of reverse osmosis (RO) membranes. The anodophilic biofilm that developed on the graphite tissue anode could detect acetate as the model AOC to concentrations as low as 5 µM (120 µg/L of AOC), which is sufficiently sensitive as an online biofouling risk sensor. Although the sensor was operated at a higher (+200 ± 10 mV) than the usual (‐300 mV) anodic potential, the presence of oxygen completely suppressed the electrical signal. In order to overcome this outcompeting effect of oxygen over the anode as electron acceptor by the bacteria, hexacyanoferrate (HCF(III)) was found to enable the development of an adapted biofilm that transferred electrons to HCF(III) rather than oxygen. As the resultant of the reduced HCF(II) could readily transfer electrons to the anode while being re‐oxidised to HCF(III), the marine MFC biosensor developed could be demonstrated to work in the presence of oxygen unlike traditional MFC. The possibility of operating the marine MFC in batch or continuous (in‐line) mode has been explored by using coulombic or potentiometric interpretation of the signal. Biotechnol. Bioeng. 2014;111: 2412–2420. © 2014 Wiley Periodicals, Inc.